Evaluation of Awareness, Knowledge, Attitude and Practices Related to Toxoplasmosis Among Females in Algeria - Mohamed Lounis; Samah Aissaoui; Fatima Ghouissem; Karim Souttou (Veterinary Sciences)
Toxoplasmosis is a major veterinary and public health issue affecting humans and animals, where felids represent the definitive hosts of the causative agent Toxoplasma gondii. While the infections are mostly asymptomatic, the disease could be severe in immune-compromised patients and pregnant women. This study was conducted to evaluate the level of knowledge, practice, and attitude toward this disease among a sample of Algerian women. A cross-sectional poll was conducted between 25 March and 28 August 2024, using a self-administered questionnaire. Results showed that only 53% of the 545 respondents heard of the disease before this survey, and being married increased the odds of awareness (AOR: 3.597 95% CI: 1.598–8.099). Among those who heard of the disease (288 women), 52.7% correct responses were obtained with varied frequencies regarding the mode of transmission and symptoms. The participants were aware of the role of cats as a source of contamination for humans (83.3%) and the common routes of transmission, including contact with cat feces (83.7%) and the consumption of undercooked meat (75%), but the role of unpasteurized milk from infected animals (40.3%), untreated water (35.8%), and blood transfusions (26.4%) was not well understood. The majority of participants ignored symptoms such as skin rashes (29.2%) and swollen lymph nodes (36.5%), as well as sequelae including mental impairment (32.3%) and eyesight issues (35.1%). Results showed also a high rate of appropriate practices and positive attitudes, where 90.3% of the participants said they were in favor of any action that intended to control toxoplasmosis. These results suggest the need to increase the level of awareness of Algerian women regarding this disease.